Adecuación de un protocolo de auditoría de redes Wi-Fi 802.11n/ac para campus universitarios aplicado a la red inalámbrica de la Facultad de Ingeniería de la Universidad Nacional de Colombia (2020)
The purpose of this work is to present a Wi-Fi network audit protocol that allows the user to execute a list of measurements and obtain a view of the quality of communication in the wireless network. A documentary review was carried out and then contrasted with the results taken in the testing scenario in the School of Engineering of the Universidad Nacional de Colombia (UNAL). This allowed establishing the list of activities and data to be recommended to perform the wireless network audit. Once the tests were defined, an audit of the Wi-Fi network of the School of Engineering of the UNAL was carried out in 53 measurements in the same number of points, distributed in buildings 401, 453 and 454. As main results of the audit, it was found that in the mentioned buildings, the 2.4 GHz band has high levels of interference, much more than the 5 GHz band. The UNAL statically uses channels 1, 6 and 11 of the 2.4 GHz band to radiate ESSIDsLikewise, in the 5 GHz band they use around 13 different channels. Given the above, connectivity tests through the ICMP protocol and throughput tests to the internet have better results in connections over the 5 GHz band.